IDENTIFIKASI BAKTERI Escherichia coli PENGHASIL Extended Spectrum β-Lactamase DARI SWAB RECTAL SAPI PERAH MENGGUNAKAN METODE VITEK-2 DI KUD TANI WILIS SENDANG KABUPATEN TULUNGAGUNG - Syah Putra, Akyun Rozaqi; Effendi, Mustofa Helmi; Koesdarto, Setiawan; Suwarno, Suwarno; Tyasningsih, Wiwik; Soelih Estoepangestie, Agnes Theresia (Journal of Basic Medical Veterinary, 2019)
Antibiotic resistance in animals and humans has become a global problem that needs attention. The use of antibiotics in inappropriate on food-producing animals can lead to resistance many of the pathogenic bacteria to the various types of antibiotics, one of which is the Escherichia coli (E. coli) which produces extended spectrum β-lactamase (ESBL). The aim of this study was to isolate and identified ESBL- E. coli isolate from dairy cow rectal swabs in Sendang, Tulungagung district using the Vitek-2 method. The number of rectal swab samples used in the present study was 50. The result of the study showed that from all of the samples could be isolated and indentified E. coli, based on the colony characteristics on EMBA and biochemical test. Based on the double disc synergy test method using antibiotic disc amoxicylyn-clavulanate, ceftriaxone, aztreonam, ceftazidime and cefotaxime, 10 isolates could be identify els ESBL- E. coli. furthermore 3 out of 10 isolates DDST positives were confirmed ESBL- E. coli using Vitek-2 method.